Identifikasi Keberadaan Mikroplastik Pada Caranx sexfasciatus Yang Dibudidayakan Di Perairan Teluk Ambon Dalam - Novianty Tuhumury; Heryan S. Pellaupessy (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
The plastic waste production is continuing to increase in waters and has become a problem worldwide. This material, in particular for the size less than 5mm, called microplastic, has been polluting the environment and humans. The aim of this research, therefore, is to identify the presence of types and amount of microplastics in Caranx sexfasciatus cultivated in Ambon Bay waters. The research was conducted in April 2020 in some floating cages as a sampling site located in the Inner Ambon Bay. A purposive sampling method was applied to collect data. The types and amount of microplastics were analysed in zoology laboratory, Mathematics and Science Faculty University of Pattimura (FMIPA Unpatti). Data analysis was carried out by displaying the type and number of microplastics and discussed further. The result revealed that there were types of film and fiber with 95 particles and 685 particles, respectively. The presence of these two types of microplastics is due to the waste disposal activities that derive from the adjacent community and are carried away by tidal currents.